Art Back Then (Memories) - Candido, Antonio (Revista do Instituto de Estudos Brasileiros, 2012)
Triggered by jolts of memory, this account by Antonio Candido revisitsthe atmosphere of artistic renewal that took hold in São Paulocity in the second half of the 1930s and which extended throughoutsubsequent decades. Recalling important exhibitions held in thecity, Candido evokes the main players of the time and the social lifeenjoyed by the city’s artists and intellectuals. In this text, a personalglance back in time coincides with a watershed in the aesthetic tasteof the day.